Vitamin C deficiency as a cause of mortality and morbidity in intensive breeding guinea pigs and their treatment - Olazábal L., Juan (2020)
The problem of morbidity and mortality of guinea pigs in a farm in the province of Trujillo, La Libertad region, is described. Due to vitamin C levels, blood and lesions, a deficiency of vitamin C was diagnosed and therefore alfalfa ad libitum was supplemented during 21 days in four animals on days 0, 1, 7, 14 and 21 of the supplementations. The increase in blood ascorbic acid levels was observed from the first day of the supplementation and its normalization at the end of the evaluation period. Moreover, the complete recovery of body condition in the evaluated animals.